PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN DAN NET INTEREST MARGIN TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Oktavianus M., Charlie (Katalogis, 2016)
This study aims to know the development and determine the influence of capital adequacy ratio, loan to deposit ratio, non-performing loan, and net interest margin on the profitability of banking companies listed on Indonesian stock exchange in 2010-2014. Its population consist of 32 banking companies; and based on purposive sampling technique, there are 15 companies selectedÂ as the researchâ€™s subjects. Technique of analysis is multiple linear regressions analysis. The result shows that loan to deposit ratio and net interest margin partialy has significant influence on profitability, meanwhile capital adequacy ratio and non-performing loan has insignificant influence on profitability. The ability of influence of four indicators towards profitability is 54,9%, and the remining is influenced by other factors that are not stuied.